ANALISA PENGARUH PENGGANTIAN KWH METER PASCABAYAR TUA TRAFO HL237 TERHADAP EFEKFIVITAS KWH JUAL DI ULP NGANJUK - Trisno Sanyoto; Muhammad Septian Wijaya; Agus Subandono; Setyo Hartono (LPPM Politeknik Pratama Kendal, 2023)
The magnitude of electricity consumption in the service area of PT. PLN (Persero) ULP Nganjuk has become a serious concern for the company. High levels of electricity usage require accurate measurement to ensure proper energy transactions and reliable revenue calculations. PT. PLN (Persero) ULP Nganjuk aims to prevent errors at energy transaction points, particularly at kWh meters that are categorized as old due to long periods of use. Aging kWh meters tend to experience a decline in performance and accuracy, which can result in electricity consumption not being recorded correctly. This condition may lead to inaccurate energy transactions and potential revenue losses for the company. To achieve more accurate and reliable energy transaction data, PT. PLN (Persero) ULP Nganjuk is actively optimizing the replacement of old kWh meters with newer and more modern units. Through this replacement program, it is expected that electricity consumption can be measured precisely, energy transactions can be calculated accurately, and unrecorded or miscalculated energy usage that affects company income can be significantly minimized.